Progress on the research and development of plague vaccines with a call to action - Williamson, E. Diane; Kilgore, Paul B.; Hendrix, Emily K.; Neil, Blake H.; Sha, Jian; Chopra, Ashok K. (npj vaccines, 2024)
There is a compelling demand for approved plague vaccines due to the endemicity of Yersinia pestis and its potential for pandemic spread. Whilst substantial progress has been made, we recommend that the global funding and health security systems should work urgently to translate some of the efficacious vaccines reviewed herein to expedite clinical development and to prevent future disastrous plague outbreaks, particularly caused by antimicrobial resistant Y. pestis strains. Content includes material subject to Crown Copyright © 2024.This is an open access article under the Open Government License ( http://www.nationalarchives.gov.uk/doc/open-government-licence/version/3/ ).